Novel facial characteristics in congenital rubella syndrome: a study of 115 cases in a cardiac hospital of Bangladesh - Nurun Nahar Fatema Begum (BMJ Paediatrics Open)
Objective To establish novel facial characteristics unique to congenital rubella syndrome (CRS) as prediagnostic criteria to supplement disease diagnosis in patients with or without a history of maternal rubella infection.Design An analysis of 115 CRS case series (2018–2020) based on the presence of any of the triad features.Setting Outpatient department of a tertiary care referral cardiac hospital in Dhaka, Bangladesh.Participants In total, 115 participants (53.1% men) were enrolled. Participants underwent echocardiography if they presented with suspected cardiac symptoms along with deafness, cataract or microcephaly.Main outcome measures Age, sex and socioeconomic status of the participants; history of maternal vaccination and infection; facial characteristics unique to CRS (triangular face, prominent nose, wide forehead and a whorl on either side of the anterior hairline) named ‘rubella facies’ and frequency of systemic involvements in CRS.Results The median patient age was 2 years. The income of 50.4% of the participating families was <US$1500. Further, 32 mothers (27.8%) were infected with rubella during the first trimester of pregnancy, 15 (13.0%) during the second trimester and 3 (2.6%) during the third trimester. The remainder (65.2%) recalled no history of infection during pregnancy. Rubella facies presented as a triangular-shaped face in 95 (82.6%) cases, a broad forehead in 88 (76.5%) and a prominent nose in 75 (65.2%). A rubella whorl was present on the right or left side of the anterior hairline in 80% and 18.2% of cases, respectively. IgG and IgM antibodies were present in 91.3% and 8.6% of children, respectively. Cataract, deafness, microcephaly, and congenital heart disease were detected in 53.0%, 75.6%, 68.6% and 98.2% of cases, respectively.Conclusions Rubella facies, a set of unique facial characteristics, can support early CRS diagnosis and treatment and may supplement the existing CRS triad.